Analisis Hubungan Kerjasama Bilateral Australia dan Fiji Dalam Bidang Keamanan Periode 2014-2019 - Siti Dhea Meutia Syarif (Universitas Airlangga, 2020)
This study analyzes Australia and Fiji's bilateral cooperation in thesecurity sector for the 2014-2019 period. Entering the democratizationera after the Fiji Coup in 2006, the relationship between Canberra andSuva seems to be getting better. Several regional and even internationalsecurity initiatives were seen as being encouraged. This paper then arguesthat the convergence of interests between the two can be attributed to thesimilarity of perceptions in terms of regional and international defense,which is increasingly prevalent in the era of democratization in Fiji. Thispaper begins by describing the methodology and theoretical framework offoreign policy analysis used to analyze this phenomenon. The next sectionprovides background on contemporary relations between Australia andFiji and analyzes how their dynamics led to the collaboration in question.This paper ends by analyzing the prospects for the resilience of bilateralrelations between the two countries in the future with the proliferation ofnew security challenges.